2014
DOI: 10.1002/2013jc009739
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between total alkalinity in surface water and sea surface dynamic height in the Pacific Ocean

Abstract: Improved spatial and temporal representation of total alkalinity (TA) is expected to be an important component in monitoring changes in the oceanic carbon cycle and acidification over the coming decades. For this reason, previous authors have sought to develop and apply empirical methods to characterize TA in the surface ocean. However, there are regions such as the North Pacific that have proven difficult to successfully represent through empirical relationships based on temperature and salinity with linear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 23 publications
2
48
1
Order By: Relevance
“…From these data, we calculated AOU, DIC normalized at S = 35 (nDIC), pH in total scale at in situ temperature, Ω arag , and preformed nDIC. Such calculation is justified because our observations (Midorikawa et al, 2010;Takatani et al, 2014) have indicated that nTA in the surface water is almost invariable in latitude and time in the western North Pacific subtropical region and is vertically uniform from the sea surface to the STMW depth. Such calculation is justified because our observations (Midorikawa et al, 2010;Takatani et al, 2014) have indicated that nTA in the surface water is almost invariable in latitude and time in the western North Pacific subtropical region and is vertically uniform from the sea surface to the STMW depth.…”
Section: Methodsmentioning
confidence: 95%
“…From these data, we calculated AOU, DIC normalized at S = 35 (nDIC), pH in total scale at in situ temperature, Ω arag , and preformed nDIC. Such calculation is justified because our observations (Midorikawa et al, 2010;Takatani et al, 2014) have indicated that nTA in the surface water is almost invariable in latitude and time in the western North Pacific subtropical region and is vertically uniform from the sea surface to the STMW depth. Such calculation is justified because our observations (Midorikawa et al, 2010;Takatani et al, 2014) have indicated that nTA in the surface water is almost invariable in latitude and time in the western North Pacific subtropical region and is vertically uniform from the sea surface to the STMW depth.…”
Section: Methodsmentioning
confidence: 95%
“…Under such conditions, the direct thermal and pH influences on Mg/Ca may work in partial opposition, theoretically resulting in lower Mg/Ca variance. Total variability in sea surface pH ranges from ~0.01 to 0.03 pH units for our core‐top locations, with maximum variance in the cold tongue east of Galapagos (Iida et al, ; Takatani et al, ). In terms of Mg/Ca, this pH variability should have a much smaller impact than temperature, but it also implies that pH and temperature are not strongly additive in the equatorial Pacific.…”
Section: Resultsmentioning
confidence: 91%
“…Climatological data were calculated by averaging over 1982–2012. JMA also provided monthly mean oceanic total alkalinity estimates (from 2001) mapped with 1° resolution [ Takatani et al ., ].…”
Section: Datamentioning
confidence: 99%
“…We used the total alkalinity data to evaluate the effect of this process. Note that total alkalinity is a quasi‐conservative property, slightly affected by biological activity (e.g., formation of calcium carbonate; change in nitric acid concentration through photosynthesis) in this region [ Takatani et al ., ]. In this study, the total alkalinity data were not affected by local biological activity because they were estimated from the sea surface salinity and dynamic height fields through an empirical relationship.…”
Section: Physical Conditions Associated With Bloomsmentioning
confidence: 99%